2009
DOI: 10.1063/1.3097245
|View full text |Cite
|
Sign up to set email alerts
|

A model of threading dislocation density in strain-relaxed Ge and GaAs epitaxial films on Si (100)

Abstract: Strain relaxation in large lattice-mismatched epitaxial films, such as Ge and III-V materials on Si, introduces high threading dislocation densities ͑TDDs͒. A thermodynamic model of TDD dependence on film thickness is developed. According to this model, the quasiequilibrium TDD of a given strain-relaxed film scales down with the inverse square of its thickness. The quasiequilibrium TDDs in both Ge and GaAs films follow this model consistently. Our model predicts the lowest possible TDD of a large lattice-misma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
83
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 95 publications
(93 citation statements)
references
References 22 publications
9
83
1
Order By: Relevance
“…4(b). The density tends to be reduced with increasing the layer thickness [19], while a post-growth annealing at high temperatures (800-900°C) [18] is effective to reduce the threading dislocation density below 10 8 cm −2 , as in the bottom of Fig. 4(b) and in Fig.…”
Section: Epitaxial Growth Of Ge On Simentioning
confidence: 93%
“…4(b). The density tends to be reduced with increasing the layer thickness [19], while a post-growth annealing at high temperatures (800-900°C) [18] is effective to reduce the threading dislocation density below 10 8 cm −2 , as in the bottom of Fig. 4(b) and in Fig.…”
Section: Epitaxial Growth Of Ge On Simentioning
confidence: 93%
“…Overall, it is concluded that below a TDD of 10 7 cm −2 , no further reduction in the junction leakage current density is observed for p + n diodes compatible with the source and drain of Ge CMOS. 8 In addition, although it is advantageous to grow thicker Ge layers, as this reduces the TDD, [9][10][11] for the selective Ge epitaxial growth in shallow trench isolation ͑STI͒ wafers, the thickness of the layer is set approximately by the STI depth so that PG annealing is crucial in improving the layer quality [12][13][14][15] and the device performance. 8,16,17 It is pointed out, finally, that for thin Ge-on-Si layers, the presence of the Ge-Si heterojunction and the associated misfit defects may affect the electrical characteristics ͑leakage current and capacitance vs voltage͒ at a sufficiently large reverse bias V R .…”
mentioning
confidence: 99%
“…During the GaAs epitaxial growth procedure, some stacking faults for GaAs on Si multiply or self-annihilate. A previous report indicated that a threading dislocation density of above 10 7 cm −2 for a 900 nm-thick epilayer decreased to 10 6 cm −2 when the film thickness was increased to above 4 µm [21]. In this study, the use of a RNS Si(001) substrate with an aspect ratio of 4.7 effectively reduced the number of thin-film dislocations for small epilayer thicknesses (<1 µm).…”
Section: Resultsmentioning
confidence: 69%